Settlement of Traffic Accident Cases through a Restorative Justice Approach: : A Study at the Traffic Accident Unit of Polresta Bukittinggi - Putri Millenia; Syaiful Munandar (Fakultas Hukum Universitas Djuanda, 2026)
Traffic accidents (traffic accidents) are one of the problems in the city of Bukittinggi. Resolving cases through litigation is often considered less effective in restoring justice, social harmony and the rights of victims. The Restorative justice approach offers an alternative resolution to traffic accidents that focuses on restoring the relationship between the victim and the perpetrator. This research aims to determine the process of resolving traffic accident cases using a Restorative justice approach along with the obstacles that exist at the Bukittinggi Police.The results of the research show that the Restorative justice approach at the Bukittinggi Police has succeeded in resolving several traffic accident cases by reaching an agreement between the victim and the perpetrator. However, there are also several obstacles that underlie the failure of Restorative justice, such as the lack of evidence due to inadequate facilities at the crime scene and the imbalance in the nominal amount of compensation that the perpetrator cannot afford, the reluctance of the parties to resolve the case and also the lack of public awareness to provide testimony to shed light on the investigation process.